A novel approach for the valorization of wine lees as a source of compounds able to modify wine properties. (January 2021) - De Iseppi, Alberto; Marangon, Matteo; Vincenzi, Simone; Lomolino, Giovanna; Curioni, Andrea; Divol, Benoit
Abstract: Wine lees, a sludge-like material mainly consisting of yeast cells, are rich in mannoproteins. However, no reports on the extraction of mannoproteins from wine lees to be used as winemaking additives are available. This study aimed at developing efficient methods for yeast glycocompounds extraction from wine lees, and to assess their impacts when added back to wine. White wine lees were extracted using physical (autoclave and ultrasonication) and enzymatic (a β-glucanases) approaches. The autoclave extract was the richest in glycocompounds and showed the highest impact on wine tartrate stability and foaming properties. Conversely, the extracts containing less glycocompounds (ultrasonication and enzymatic) both improved wine protein stability upon heat test and had a low effect on wine foaming. In general, wine lees can be considered as a valuable source of substances to be used as winemaking additives thus opening the way to a new type of exploitation of these by-products. Graphical abstract: Image 1 Highlights: Yeast lees recovered after wine fermentation were extracted with three different methods. Extracts, showing different composition, were rich in glycocompounds. When added back to wine extracts impacted its stability and foaming properties. Wine lees a winemaking by-product, have the potential to be better exploited.